Measurements of Inorganic Materials and Acidity in Plantation Teakwood - Ganis Lukmandaru; Rudy Nur Hidayah (Wood Research Journal, 2018)
Information concerning ash materials and acidity (pH values) within the wood of teak (Tectona grandis L.f.) plantations is especially limited. Samples taken from the stands of Perhutani plantation (Madiun and Randublatung) and community forests in Kulon Progo (Temon and Kalibawang) were analyzed to determine the ash content, metallic elements constituting the ash fraction, as well as pH values. The ranges of ash content were 0.55-3.88% whereas acid insolube ash content (silica/silicates) were 0.12-2.45%. The main four inorganic elements in wood were assayed by atomic absorption. The levels of these metals ranged from 340-4774 ppm for calcium, 17-4399 ppm for potassium, 143-1676 ppm for magnesium, and 0247 ppm for iron. Further, the pH values varied from 5.33-7.25. Differences of inorganic variables and pH values in wood were found between trees of different growth-site and radial position. The variation among the different sites was significant in the contents of silica, calcium, magnesium, potassium, and sodium while the effects of radial direction were significant in the silica and potassium levels. Ash content was positively correlated with acid insoluble ash (r = 0.77) and potassium content (r = 0.47). Furthermore, pH values were positively correlated with the magnesium content (r = 0.65) and negatively correlated with potassium (r = -0.49) and sodium contents (r = -0.55). A description of the chemical properties of the soil, however, was not sufficient in determining whether there was a relationship between the levels of metal elements or pH values in the wood and in the soil.